Implementasi Penerapan Undang-Undang Nomor 13 Tahun 2006 tentang Perlindungan Saksi dan Korban (Sudi di Polres Kuningan) - Haris Budiman; Gios Adhyaksa (UNIFIKASI : Jurnal Ilmu Hukum, 2015)
Article 1 (1) of the 1945 Constitution states that, Indonesia is the law of the State in the form of Republic. Therefore, the provisions of the applicable legislation and set the life of the Indonesian nation comes from the law, whether written or unwritten law. One runway is used as basic guidelines in order to achieve justice for all Indonesian people, especially in the field of law, set forth in Article 27 paragraph (1) of the Act of 1945, which reads, "All citizens are equal before the law and government and must uphold the rule of law and without exception. " Protection of witnesses reporting the crime of pornography, the identity of a witness, obviously very secret and confidential examined by the police, even on a trial judge has no right to bring a witness, before the trial because the reporter's identity confidentiality is strictly protected by the Law No. 44 Year 2008 on pornography.Â  Factors that became penghamabat the police to provide protection against the crime of pornography reporting, that one of the eligibility period and the cost to hold the protection of witnesses and victims must require substantial funds, although basically the police have been very ready to implement the law , subject to the government in terms of a special budget for the program of protection, especially for operational costs in the field. Â Keywords: Crime, Pornography, Witness, Protection.Â